Growth and genetic stability of the ts-1 mutant of respiratory syncytial virus at restrictive temperatures. - Schnitzer, T J (1976)
An in vitro study was performed to define in greater detail those factors which favored the growth of the ts-1 mutant of respiratory syncytial virus under restrictive conditions and the emergence of genetically altered virus with decreased temperature sensitivity. Replication of ts-1 occurred at each of the restrictive temperatures of 37, 38, and 39 C, even through plaque formation was not observed. The level of virus growth under restrictive conditions was inversely related to the incubation temperature and directly related to the multiplicity of infection. These relationships appeared to reflect the effect of restrictive temperature in reducing the quantity of virus produced and released from an infected cell. Under restrictive conditions the production of genetically altered virus which exhibited reduced temperature sensitivity was directly related to the multiplicity of infection and inversely related to temperature. Production of genetically altered virus was not observed under permissive conditions.